Equivalent Circuit Parameter Measurement of Multiphase Induction Machine by Exploitation of Space Harmonic Relations - Omer Ikram Ul Haq; R. S. Kanchan; Sjoerd G. Bosga; Luca Peretti (IEEE Access)
A multiphase induction machine model using vector space decomposition provides insights into many space harmonics through decoupled reference frames. In order to utilize this potential of the multiphase machine, the parameters of each vector space must be identified. These parameters are usually identified using standard no-load and locked rotor tests of each torque-producing vector space. However, these tests do not provide a method for identifying stator leakage inductances, which have comparable magnitudes to the magnetizing inductances for higher-order vector spaces. Thus, the magnetizing current cannot be neglected during the locked-rotor test. This paper proposes an accurate method for identifying the T-model parameters of a multiphase induction machine, which can be conveniently translated into the model of choice. The proposed method use harmonic relations to segregate the stator leakage inductance from the total stator inductance, enabling accurate locked-rotor and partial-load tests for the measurement of rotor side parameters. Lastly, a 9-phase induction machine is used for the evaluation of the proposed parameter measurement method. These measured parameters are used for the field-oriented control of each torque-producing vector space, whose performances are analyzed by quantifying the measured output torque error and linearity.